ACID MINE DRAINAGE MANAGEMENT RELATED TO THE WASTE ROCK TREATMENT LAYERING AND BLENDING ON BENGALON SITE OF PT. KALTIM PRIMA COAL - Puspitasari, Retno
Mining activity is always associated with its impact on the environment, and that is often a problem that Acid Mine Drainage (AMD). To get the coal layers done stripping overburden which produce residual rocks (waste rock) in very large volumes. The remaining rocks containing sulphide material that has the potential to oxidize if it reacts with water and oxygen. This led to the formation of acid mine drainage. Acid mine drainage can dissolve metals contained in the waste rock, when it is carried away by the water will also degrade water quality. Mine acid water production is difficult to stop at all, therefore it needs intensive management by applying the method of stockpiling of material waste rock. Classification of geochemical analysis performed using material (static test) test method by applying the NAG (Net Acid Generation) and NAPP (Net Acid Producing Potential) obtained from the calculation of acid-base (Acid Base Account). Calculation of acid-base (ABA) was conducted to determine the qualitative measure of the difference between the capacity of the sample in the form of acid (Maximum Potential Acid or MPA) and its capacity to neutralize acid (Acid Neutralizing Capacity or ANC). Two measures of acid-base balance (ANC and MPA) calculated to get the potential acid production Neto (NAPP). The next step, the application of the prevention of the formation of AMD do with kinetic test using column leaching (free draining leach column test). The treatment is applied for 6 weeks. Wet and dry conditions are applied against the rocks on the column, with the treatment of the material blending and layering PAF and NAF with compositions that have been determined. Layering is applied by placing PAF material under NAF material layers. While blending is done by mixing the material evenly to the NAF and PAF (homogeneous). Watering is done per week on both the treatment to get water handy to know leach change parameter values of water quality (pH and metal concentrations). This is done to test the techniques of control and handling of the AMD. Based on the analysis of kinetic test water leaching, treatment of mixing (blending) shows a greater pH value and relatively more stable when compared to the behavior of layering. As shown in the material composition of the PAF-NAF PAF20%: NAF80% in the first week, layering of vi 2.95 pH (acidic) pH and blending of 5.15 (neutral). On the sixth week, pH on layering up pretty significant to pH 7.35 and blending are at the value 6,09. On the composition of the PAF is greater i.e. PAF80%: NAF20%, pH of layering in the first week of 2.37 and blending of 3,86 pH. Until the sixth week of the pH value of 2.65 in layering and blending in the pH value of 3,94. Although both the treatment has a pH acid, but pH blending is greater than pH layering. These phenomena occur because on the blending, the presence of the neutralizer material NAF distributed evenly on the space between rock grains, functioning as effective in neutralizing when the acidic water is formed. While in the layering of material functions as a barrier coating of NAF influx of oxygen just started functioning effectively in the second week of treatment. PH values that tend to result in small causing of dissolve metal from the waste rocks material. This is demonstrated by the composition of the PAF20%: NAF80% in the first week, the concentration of Fe on layering amounting to 20,96 mg/l and dropped to 7,34 mg/l at the sixth week. So also on the blending, the value of the first week worth of 21,49 Fe mg/l and dropped to 17.30 mg/l. in both treatments, the same thing happened on metal Mn concentration decreased with the rise in the value of pH. While in metals Al, its concentration increases over time, this is because Al has amfoter. From these phenomena, blending may be an option especially on the composition of PAF40%: NAF60%. It is with regard to the availability of material remnants of waste rock PT. KPC, where the volume of NAF of 73% and 27% of PAF material.